Dampness and mold exposure in buildings as a risk factor for health effects - Huong, Pei Zam; Zainal Abidin, Emilia; Karuppiah, Karmegam; Salit @ Sinon, Mohd Sapuan (Malaysian Public Health Physicians Association, 2017)
This study aims to review existing studies on the relations between indoor dampness and mould in different public occupied buildings with the risk of adverse health effects among both children and adults. This study specifically focused on the dampness-related problems from countries with tropical climate. A systematic literature search of ScienceDirect, PubMed, Google Scholar and Wiley Online Library from 2000 through December 2015 was conducted. Furthermore, the reference lists of recent reviews and of relevant articles were identified in our search. Cross-sectional, case-control, and cohort studies in children or adults were selected according to a priori criteria. The search yielded a total of 18 studies on damp buildings, dampness and mould in buildings and indoor mould. Dampness and mould exposure in buildings is a risk factors for respiratory symptoms, wheeze, cough, bronchitis, rhinitis, eczema and upper respiratory tract infection as well as general symptoms such as headache and tiredness. Evident strongly suggested increased asthma development and exacerbation of current or ever diagnosis of asthma in children. Based on the results of the review, indoor dampness and mould problems in buildings are associated with substantial and increases in prevalence of a variety of respiratory and asthma-related health outcomes.